2016
DOI: 10.1038/srep34655
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant indatraline induces autophagy and inhibits restenosis via suppression of mTOR/S6 kinase signaling pathway

Abstract: Indatraline is an antidepressive agent and a non-selective monoamine transporter inhibitor that blocks the reuptake of neurotransmitters (dopamine, serotonin, and norepinephrine). In this study, we report that indatraline induces autophagy via the suppression of mTOR/S6 kinase signaling. Autophagy induction was examined by a cell-based high content screening system using LysoTracker, which was followed by monodansylcadaverine staining and transmission electron microscope observation. Indatraline increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
(39 reference statements)
3
25
0
Order By: Relevance
“…The molecular mechanism by which AMPK regulates autophagy has been revealed in previous reports. AMPK regulating autophagy is dependent or independent of mTOR, through AMPK-mTOR-S6 K and AMPK-ULK1 signaling pathways, respectively [ 22 , 23 ]. mTOR activity is negatively modulated by AMPK, but mTOR inhibition associates improved autophagy, that is the reason why mTOR selective inhibitor Rapamycin is usually used as autophagy agonist.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism by which AMPK regulates autophagy has been revealed in previous reports. AMPK regulating autophagy is dependent or independent of mTOR, through AMPK-mTOR-S6 K and AMPK-ULK1 signaling pathways, respectively [ 22 , 23 ]. mTOR activity is negatively modulated by AMPK, but mTOR inhibition associates improved autophagy, that is the reason why mTOR selective inhibitor Rapamycin is usually used as autophagy agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the biolimus-induced autophagy contributes in enhancing cell cycle arrest and consequently inhibiting neointimal hyperplasia in vivo as effectively as do sirolimus and everolimus. Similarly, we have shown that a chemical compound targeting monoamine transporter induces autophagy in VSMCs, which sufficiently inhibits neointimal hyperplasia in the injured carotid vessels 52 . In addition, we cannot exclude a possibility that the enhanced 4E-BP1 function also contributes to cytostatic effect of biolimus because the 4E-BP1 de-phosphorylation inhibits cell proliferation 53 .…”
Section: Discussionmentioning
confidence: 73%
“…As S6 K is a well‐characterized downstream effector molecule of mTORC1, we detected the levels of S6 K phosphorylated at Thr389 for mTOR activation . LC3B‐II, Beclin1 and SNAP29 are commonly used as markers of autophagy .…”
Section: Resultsmentioning
confidence: 99%